2013
DOI: 10.1111/pin.12109
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid binding protein 7 as a marker of glioma stem cells

Abstract: Glioblastomas are the most aggressive brain tumors. Glioblastoma stem cells (GSCs) are thought to be responsible for the recurrence, chemoresistance, and poor prognosis of glioblastoma. Fatty acid binding protein 7 (FABP7), which is a cellular chaperone for a variety of omega-3 fatty acids, is a known marker for neural stem cells. In this study, using a newly developed anti-FABP7 antibody and patient-derived GSC lines, we evaluated the expression of FABP7 in GSCs. Using immunocytochemistry, Western blotting, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 36 publications
2
38
0
Order By: Relevance
“…More recently, FABP7 has been recognized as a NOTCH1 target with a key role in the maintenance of radial glia cells with NSC properties . Interestingly, FABP7 is a shared NOTCH1/SOX10 target that marks neural stem cells in the subventricular CNS zone, as well as CSC in glioblastoma . Fatty acid‐binding protein 7 is coexpressed with SOX10 in ACC and basal‐like breast cancers, and in these tumor types FABP7 expression serves as a diagnostic marker associated with poor prognosis .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, FABP7 has been recognized as a NOTCH1 target with a key role in the maintenance of radial glia cells with NSC properties . Interestingly, FABP7 is a shared NOTCH1/SOX10 target that marks neural stem cells in the subventricular CNS zone, as well as CSC in glioblastoma . Fatty acid‐binding protein 7 is coexpressed with SOX10 in ACC and basal‐like breast cancers, and in these tumor types FABP7 expression serves as a diagnostic marker associated with poor prognosis .…”
Section: Resultsmentioning
confidence: 99%
“…[136][137][138][139][140] Interestingly, FABP7 is a shared NOTCH1/SOX10 target 136,141 that marks neural stem cells in the subventricular CNS zone, as well as CSC in glioblastoma. [142][143][144] Fatty acidbinding protein 7 is coexpressed with SOX10 in ACC and basal-like breast cancers, 97 and in these tumor types FABP7 expression serves as a diagnostic marker associated with poor prognosis. 79,145 Although the mechanism of FABP7 activity in cancer or CSC maintenance is not well described, activation of FABP7 in cancers increases fatty acid uptake resulting in enhanced cell survival and protection against reactive oxygen species.…”
Section: Fatty Acid-binding Proteinmentioning
confidence: 99%
“…Within the central cell cluster, a subset of cells expresses other stem cell-associated genes, such as isl1 and fabp7a (clusters 7, 9; Fig. 1K; (Kim et al, 2016;Makarev and Gorivodsky, 2014;Morihiro et al, 2013;Shin et al, 2007)). In addition, members of the retinoic acid pathway, such as crabp2a, dhrs3a and rdh10a are restricted to clusters 7 and 9 ( Fig.…”
Section: Single Cell Rna-seq Reveals Support Cell Heterogeneitymentioning
confidence: 99%
“…Most kinds of cancers contain a subset cells which have an indefinite self-renewal potential and could differentiate multidirectional, those cells are called cancer stem cells (CSCs) [2]. Some recent studies reported that the CSCs in gioblastoma (GSCs) had been isolated and identified successfully [3,4].…”
Section: Introductionmentioning
confidence: 99%